Preserving Community Interests in Ocean Governance towards Sustainability - Zou, Keyuan; Chang, Yen-Chiang (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue is designed to discuss and examine relevant legal issues concerning ocean governance in the context of the United Nations Sustainable Development Goals (SDGs) for the long-lasting benefits of the international community. It will cover, inter alia, the safety of navigation and maritime security, the sustainable use of marine resources (living and non-living), marine environmental protection, climate change, and marine scientific research.